The last mughal - Dalrymple, William (Penguin Books New York, 2007)
The Last Mughal: The Fall of a Dynasty, Delhi, 1857 recounts the final days of the Mughal Empire through the life of its last emperor, Bahadur Shah Zafar, and the 1857 Indian Rebellion against British rule.